9(9-k)=6k-1

Simple and best practice solution for 9(9-k)=6k-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(9-k)=6k-1 equation:


Simplifying
9(9 + -1k) = 6k + -1
(9 * 9 + -1k * 9) = 6k + -1
(81 + -9k) = 6k + -1

Reorder the terms:
81 + -9k = -1 + 6k

Solving
81 + -9k = -1 + 6k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-6k' to each side of the equation.
81 + -9k + -6k = -1 + 6k + -6k

Combine like terms: -9k + -6k = -15k
81 + -15k = -1 + 6k + -6k

Combine like terms: 6k + -6k = 0
81 + -15k = -1 + 0
81 + -15k = -1

Add '-81' to each side of the equation.
81 + -81 + -15k = -1 + -81

Combine like terms: 81 + -81 = 0
0 + -15k = -1 + -81
-15k = -1 + -81

Combine like terms: -1 + -81 = -82
-15k = -82

Divide each side by '-15'.
k = 5.466666667

Simplifying
k = 5.466666667

See similar equations:

| 10-32=12 | | 2(x+14)=3x+14 | | 204/x=48 | | 10+0b=550 | | -7x^3=-7 | | -4-4x=x^2 | | (x-(4-7i))(x+(4-7i))=0 | | 5/3x=1,400 | | 5/3x=2004 | | 3(x-2)=10+x-2 | | -16*(-3*2+8)= | | 100+7.50b=550 | | n/4/9=36/7 | | 25.2t=315 | | p-wx=4 | | 4200=42(p+30) | | 3(4+6w)= | | 2(y-2)-8=-2(-9y+5)-8y | | -2u^2-u-1=0 | | X/5=-123 | | 66-10x=60-x | | 8u=49 | | (2n-11)/-3=-9 | | lg(x^2-4)=2+lg(x-2) | | 30.4=-7.6(x-4.25) | | R=(12-0.5x)(36+2x) | | 332-312= | | 6x-8+2(5x+3)=-2(x+3) | | 1/2x=(-3) | | (4n-2)/7=3 | | Y=450-10x | | c-1.23=0.18 |

Equations solver categories